Questions and answers on parenting a handbook for parents, teachers, and everyone involved with children - Tan, Emma R. (Makati City Bookmark, 1995)
Purpose: This book provides "collections of factual situations covering early childhood, adolescence, marital and extramarital episodes, the single parent and coping with the death of a child."
Contents: Parenting. Newborn baby. First child. Stages of child development. Problems during adolescence. Personality development. Marriage. Death of a child. Glossary.
Keywords: Parenting -- Philippines -- Handbooks, manuals, etc; Children -- Management -- Handbooks, manuals, etc